2010
DOI: 10.3390/molecules15010374
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Preparation of 2,3,4,6-Tetra-O-acyl-Gluco-, Galacto- and Mannopyranoses and Relevant Theoretical Study

Abstract: The deacylation of glucose, galactose and mannose pentaacetates, galactose and mannose penta(3-bromo)benzoates, as well as the dealkylation of 2,3,4,6-tetra-O-acetyl and 2,3,4,6-tetra-O-(3-bromo)benzoyl methyl α-D-glucopyranosides have been studied. In addition, a computational study on the deacylation of β-D-glucose pentaacetate has been carried out with density functional theory (B3LYP/6-31G*). The anomeric effect during deacetylation and dealkylation has been clearly demonstrated in both experimental and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…At 21.5 min (Figure 3-4) a peak was observed relating to the final product (2) without one acetyl group. This was also reported by Wang et al and was explained to be related to the thermolytic condition of the BF3 reaction [233]. Previous studies have also reported 18 h reactions using the same reaction conditions described here (BF3.Et2O, DCM, RT, Fmoc-ser-OH) generating a pure yield of 5% [230].…”
Section: Design and Synthesis Of Mannosylated Building Blockssupporting
confidence: 64%
See 1 more Smart Citation
“…At 21.5 min (Figure 3-4) a peak was observed relating to the final product (2) without one acetyl group. This was also reported by Wang et al and was explained to be related to the thermolytic condition of the BF3 reaction [233]. Previous studies have also reported 18 h reactions using the same reaction conditions described here (BF3.Et2O, DCM, RT, Fmoc-ser-OH) generating a pure yield of 5% [230].…”
Section: Design and Synthesis Of Mannosylated Building Blockssupporting
confidence: 64%
“…Further, Lewis acid reaction (Figure 3-2) was chosen due to the ease of access to starting materials and shorter reaction times regarding the steps taken compared to other methods available for preparation of a mannose-serine building block. (acetylated mannosyl donor) to Fmoc-Ser-OH using BF3.Et2O in DCM at RT for 4 h generated 2 (Fmoc-serine mannosylated amino acid building blocks) as a mixture of α and β due to attack of the Lewis acid from both below (β, 25.44%) and above (α, 74.55%) [233]. For synthesis details see Chapter 2, Section 2.1.2.…”
Section: Design and Synthesis Of Mannosylated Building Blocksmentioning
confidence: 99%
“…The solvent residue was removed by distillation. The obtained product was allowed to treat with methanol to obtain final product [18]. The product was crystallized by using ethanol.…”
Section: Synthesis Of Acetylated Nucleoside From Glucosementioning
confidence: 99%
“…In this regard, aminoglycosides showed the primary advancement regarding their demand and utilisation as anticancer drugs. Monosaccharides increase tumor consumption compared to normal cells, resulting in increased intracellular uptake of tumor cells [8,9]. Activation and release of glycogen-mediated drugs to the target site can be accelerated by a glycoside attached to a specific antibody.…”
Section: Introductionmentioning
confidence: 99%